Peningkatan Sikap Peduli Lingkungan Anak Prasekolah Melalui Bermain Peran “Aku Sayang Bumiku” - Tarnoto, Nissa; Martani, Wisjnu (Universitas Ahmad Dahlan, 2014)
ABSTRACTNow global warming becomes the attention of all over the world. Global warming is probably caused by the increasing of the concentration of the greenhouse effects which is due to human activities. There are a lot of Indonesia people who do not care about their environment. Indonesia has to be aware of global warming such as the changing of the extreme weather, flood, clean water crisis, disease. Related to those problems, it needs to be appreciated the attitude of care for the environment since early. The objective of this research is to know whether the method of role playing is able to increase the attitude of care for the environment at the early stage of children. This research involved 29 preschool students. They were divided into 2 groups, control group and experiment group. The hypothesis was that there was the different attitude between two groups. The method which was used in this research was non – randomized pretest – posttest control only group design. From the statistical analysis using Paired Sample t – test showed that therewas significantly difference for the experiment group before and after the conduct of role playing method “ I Love my Earth” (t=11,168, p=0,000). Statistical analysis using Independent sample ttest with score gain (t = 9,350, p= 0,000) showed that there was significantly different attitude of care for the environment between the experiment group and the control group ( t = 9,350, p =0,000).Key word : The attitude of care for the environment, role playing, preschool